2023
DOI: 10.14744/tjtes.2022.33332
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ranson score, computed tomography severity index and CRP criteria in risk stratification on the day of hospital admission in patients with acute pancreatitis: A cross-sectional analysis

Abstract: 65-85% of cases not requiring specific treatment or resulting in sequelae, the remaining may suffer from severe attacks progressing to systemic inflammatory response syndrome (SIRS) with a high morbidity and mortality. [3][4][5][6] Hence, the early assessment of severity of disease through risk stratification,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Therefore, since these parameters used in daily practice are increased in many diseases, their use may not be safe in predicting severe pancreatitis, just like CRP, as seen in our results. [12,33–35]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, since these parameters used in daily practice are increased in many diseases, their use may not be safe in predicting severe pancreatitis, just like CRP, as seen in our results. [12,33–35]…”
Section: Discussionmentioning
confidence: 99%
“…Our study is significant as it is the first to evaluate SAL-β levels in patients with AP. [8][9][10][11][12] While most cases of AP follow a mild course, severe forms demand increased attention due to their high morbidity and mortality. Several single and multiparametric scoring systems have been defined to assess the severity of the disease by, incorporating laboratory parameters and physiological and radiological assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, they cannot be displayed graphically. [9,10] Herein, more attention was paid to the Ranson score as it is the most widely used and has maintained its clinical effectiveness for years. In clinical practice, the data demonstrated that the imaging findings of the pancreas on an early computerized tomography (CT) scan could only reflect the severity at the time of admission, but could not predict the prognosis of HTG-AP.…”
Section: The Present Study Was Supported By the Foundation Of Health ...mentioning
confidence: 99%